Percheron Artery Obstruction Syndrome: A Rare Case of Diffuse Bitalamic Ischemia. Case Report (Revista de Medicina Clinica, 2024)
Percheron artery syndrome is a rare entity, its prevalence being unknown, with the Percheron artery being an anatomical variant of the paramedian artery in which a single perforating artery supplies both thalamic nuclei, causing a bilateral thalamic infarct when occluded. A classic clinical triad is described as: vertical gaze palsy, consciousness and cognitive-behavioral alterations, which despite being a non-specific clinical condition and the small number of cases known to medical personnel, we present a case of a woman of A 43-year-old woman who had an onset of highly varied neurological symptoms, finding the classic triad as late symptoms and confirming it by means of an imaging study after having been transferred multiple times to different medical institutions.
Keywords: Percheron; Bilateral thalamic infarctions; Ischemic stroke; Percheron artery; Thalamic infarct; Clinical case